No sex difference in mental fatigue effect on high-Llvel runners` aerobic performance - Ribeiro Lopes, T.; Machado Oliveira, D.; Brandao Simurro, P.; Teruo Akiba, H.; Nakamura, F. N.; Okano, A. H.; Machado Dias, A.; Moreira Silva, B. (Medicine & Science in Sports & Exercise, 2020)
Purpose: Some evidence suggests that sedentary women may be more vulnerable to cognitive task-induced mental fatigue. Mental fatigue, in turn, may worse aerobic exercise performance, presumably via increased perceived effort. However, it remains unclear whether acute mental fatigue induction increases perceived effort and worsens endurance performance in high-level professional athletes and whether such effects are influenced by sex. Methods: We studied 30 athletes (15 women and 16 men) in a single-blinded, randomized, controlled and crossover protocol. In separate visits, athletes either performed a 45-min cognitive task (Stroop`s color-word conflict test) to induce mental fatigue or watched a 45-min documentary as control. Then athletes performed a time-to-exhaustion test on a treadmill. Results: Perceptual measures and cognitive performance indicated that the prolonged cognitive task induced a similar mental fatigue state in women and men. Cardiorespiratory and metabolic responses to the TEE did not change with mental fatigue in both sexes. Mental fatigue increased perceived effort during the time-to-exhaustion test, anticipated attainment of maximal effort, and shortened time to exhaustion similarly in women and men (mean ± SE, -27.3 ± 20.9 s for women vs -26.7 ± 15.1 s for men; P = 0.98). Conclusions: The prolonged cognitive task provoked mental fatigue, anticipated attainment of maximal perceived effort, and worsened aerobic performance in professional runners with no sex differences. Although we did not contrasted athletes with nonathletes, our results suggest that being an athlete may somehow prevent women from developing greater mental fatigue and suffering more from its underlying effects compared with men.